2021
DOI: 10.1051/0004-6361/202140895
|View full text |Cite
|
Sign up to set email alerts
|

Redshift evolution of the Amati relation: Calibrated results from the Hubble diagram of quasars at high redshifts

Abstract: Gamma-ray bursts (GRBs) have long been proposed as a complementary probe to type Ia supernovae (SNe Ia) and the cosmic microwave background to explore the expansion history of the high-redshift universe, mainly because they are bright enough to be detected at greater distances. Although they lack definite physical explanations, many empirical correlations between GRB isotropic energy or luminosity and some directly detectable spectral or temporal properties have been proposed to make GRBs standard candles. Sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Therefore, the 𝐸 iso − 𝐸 p correlation is consistent for all redshift ranges. The correlation shows no significant evolution with redshifts, which is in line with Wang et al (2011) and Dai et al (2021). If the correlation evolves with evolution, the method mentioned in Dainotti et al (2022b) can be used to fit the evolutionary function.…”
Section: Testing the Evolution Of 𝐸 Iso − 𝐸 P Correlation With Redshiftssupporting
confidence: 73%
“…Therefore, the 𝐸 iso − 𝐸 p correlation is consistent for all redshift ranges. The correlation shows no significant evolution with redshifts, which is in line with Wang et al (2011) and Dai et al (2021). If the correlation evolves with evolution, the method mentioned in Dainotti et al (2022b) can be used to fit the evolutionary function.…”
Section: Testing the Evolution Of 𝐸 Iso − 𝐸 P Correlation With Redshiftssupporting
confidence: 73%
“…More recently, Khadka et al (2021) found that the Amati relation is independent of redshift within the error bars with the A220 GRB data set. Dai et al (2021) found strong evidence that the Amati relation shows no, or marginal, evolution with redshift. Tang et al (2021) found that the intercept and slope of the Amati relation for the low-z subsample and high-z subsample differ at more than 2δ.…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…LGRBs follow the E p − L iso (Yonetoku et al 2004) correlation, where E p is the peak energy of the ν F ν spectrum and the E p − E iso correlation (Amati & Frontera 2002) links the peak energy with the isotropic energy E iso . It has been proved (Nava et al 2012;Dai et al 2021) that these correlations do not evolve with redshift. Following Ghirlanda et al (2015), in our simulation we sample Equation (1), extracting a redshift, and we independently assign an E p value sampling a broken power law.…”
Section: The Modelmentioning
confidence: 99%